(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Academic integrity is a cornerstone of quality education, yet its application in English language teaching (ELT) at higher education institutions remains insufficiently explored, particularly in Central Asian contexts. This article investigates the challenges associated with maintaining academic honesty in ELT classrooms at Namangan State University, Uzbekistan. Drawing on a survey of 120 undergraduate students and 18 faculty members, the study identifies prevalent forms of academic dishonesty — including plagiarism, unauthorised use of artificial intelligence (AI) tools, and improper citation practices — and analyses their underlying causes. The findings reveal that limited awareness of institutional policies, inadequate digital literacy, and the growing accessibility of AI writing assistants are primary contributing factors. Based on these results, the article proposes a comprehensive framework incorporating curriculum-embedded integrity education, transparent AI usage policies, and formative assessment strategies. The study contributes to the emerging discourse on academic integrity in ELT and offers practical recommendations for educators and institutional policymakers.